2008
DOI: 10.1080/00365520802321170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal complaints in runners competing in a long-distance run: An internet-based observational study in 1281 subjects

Abstract: The prevalence of GI complaints during and after running was low compared with that reported in other studies, which is partly due to the definition of "symptomatic" used in our study. The risk factors associated with becoming symptomatic were identical to those in other studies. The relationship between complaints during the run and the type of complaints afterwards suggests a role of GI ischaemia in the pathophysiology of running-induced GI symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 21 publications
9
88
1
1
Order By: Relevance
“…The risk of this occurring is greater in the under-trained athlete who may experience high levels of splanchnic vascular hyper-responsiveness secondary to prolonged blood flow redistribution [15,16]. Dehydration is a risk factor and women appear to be more frequently affected [17]. For more comprehensive reviews readers are referred elsewhere [ ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of this occurring is greater in the under-trained athlete who may experience high levels of splanchnic vascular hyper-responsiveness secondary to prolonged blood flow redistribution [15,16]. Dehydration is a risk factor and women appear to be more frequently affected [17]. For more comprehensive reviews readers are referred elsewhere [ ].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms led to greater compromised carbohydrate intake during exercise and greater time to event completion during a multi-stage running event (i.e., consecutive days of prolonged strenuous exercise) ; and similar symptom manifestation is reported to be a main contributing factor for endurance event withdrawal (Hoffman and Fogard 2011;Jeukendrup et al 2000;Stuempfle and Hoffman 2015). Additionally, it has previously been observed that female runners reported higher incidence of symptoms compared with male counterparts (ter Steege et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During the recovery phase, symptoms may consist of nausea, vomiting, bloody diarrhoea and even collapse 24. The severity of the symptoms varies from ‘mild but disturbing’ to ‘severe’ and may even lead to hospitalisation and emergency surgery 2 5…”
Section: Introductionmentioning
confidence: 99%